The development of learning media "UNGGAS NANNO" on subjects of intranatal care and newborn care - Lellyawaty Lellyawaty; Rizky Vaira (JINoP (Jurnal Inovasi Pembelajaran), 2024)
Quality learning is the goal of learning. The mismatch of media in the delivery of lessons will result in the goal of learning not being achieved. In addition to teacher talks, videos, and practices in the laboratory to achieve learning objectives, it turns out that midwifery students have not mastered the related scientific foundations in subjects of intranatal care, especially providing care during labor and newborn care that has been studied. To attract students' interest and motivation in mastery, "Ular TaNGGa ASuhan PersaliNAn NOrmal (UNGGAS NANNO) or Intranatal Care and Newborn Care Snakes and Ladders Game" is needed in learning. The ADDIE model was used in research with validation subjects from expert teams and midwifery students as users. UNGGAS NANNO media is considered very worthy and very interesting in terms of the suitability of learning materials, images, and sizes, with an average score (of 92.5% and 96.8%). In addition to being feasible, UNGGAS NANNO can be used as an additional medium for learning and alternative assessments as a substitute for the final semester exam by teaching lecturers.